In Vitro Antimicrobial Properties of Recombinant ASABF, an Antimicrobial Peptide Isolated from the Nematode Ascaris suum - Zhang, Hong (American Society for Microbiology, 2000)
ASABF is a CSαβ-type antimicrobial peptide that contains four intramolecular disulfide bridges (Y. Kato and S. Komatsu, J. Biol. Chem. 271:30493–30498, 1996). In the present study, a recombinant ASABF was produced by using a yeast expression system, and its antimicrobial activity was characterized in detail. The recombinant ASABF was active against all gram-positive bacteria tested (7 of 7; minimum bactericidal concentration [MBC], 0.03 to 1 μg/ml) except Leuconostoc mesenteroides, some gram-negative bacteria (8 of 14; MBC, >0.5 μg/ml), and some yeasts (3 of 9; MBC >3 μg/ml). Slight hemolytic activity (4.2% at 100 μg/ml) against human erythrocytes was observed only under low-ionic-strength conditions. Less than 1 min of contact was enough to kill Staphylococcus aureus ATCC 6538P. The bactericidal activity against S. aureus was inhibited by salts.